2011
DOI: 10.1007/s11259-011-9487-5
|View full text |Cite
|
Sign up to set email alerts
|

Coll2-1, Coll2-1NO2 and myeloperoxidase concentrations in the synovial fluid of equine tarsocrural joints affected with osteochondrosis

Abstract: The measurement of biomarkers that reflect cartilage breakdown is a powerful tool for investigating joint damage caused by disease or injury. Particularly in cases of osteochondrosis, synovial concentrations of these biomarkers may reveal the presence of osteoarthritic changes. Coll2-1, Coll2-1 NO2 and myeloperoxidase have recently been introduced in equine osteoarticular research but comparison between the concentrations of these markers in OCD affected and healthy joints has not been made. Therefore, this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
(37 reference statements)
2
8
0
Order By: Relevance
“…They have been tested in animals [31-34] and humans [35-39]. Coll2-1 is the only one biomarker that was affected by the treatment with curcumin in this study.…”
Section: Discussionmentioning
confidence: 99%
“…They have been tested in animals [31-34] and humans [35-39]. Coll2-1 is the only one biomarker that was affected by the treatment with curcumin in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Osteocalcin, or bone Gla-protein (BGP), is a small protein synthesized by osteoblasts and odontoblasts, containing carboxyglutamic moieties and constituting the major part of non-collagenous bone matrix. Many studies demonstrated that serum osteocalcin provides a useful marker of bone metabolism in several bone diseases [ 97 ]. During the mineralization process, calcium phosphate is first deposited in matrix vesicles derived from cells dispersed throughout the hypertrophic zone, before being successively converted to hydroxyapatite.…”
Section: Pathophysiological Mechanisms Underlying Ocd Developmentmentioning
confidence: 99%
“…Synovial fluid levels of Coll2-1 were significantly elevated in tarsocrural joints affected with osteochondrosis compared with unaffected joints. 71,72 Another study compared sera of box-stall rest, pasture and trained foals. 73 Lower serum levels of CPII and higher levels of CTX-I were found in the trained foals compared with the other groups.…”
Section: Horsesmentioning
confidence: 99%